A cross-sectional study of pediatric eye care perceptions in Ghana, Honduras, and India. Issue 2 (June 2015) - Ramai, Daryl; Elliott, Ryan; Goldin, Shoshanna; Pulisetty, Tejas
Abstract Of the more than 1.4 million blind children worldwide, 75% live in developing countries. To reduce the prevalence of childhood blindness and associated diseases, attention is given to understanding the perceptions and level of awareness held by caregivers. This understanding can enable tailored health programs to reduce the global prevalence of blindness with increased efficiency. This study, which took place in Ghana, Honduras, and India, found that 95% of caregivers believed in the importance of eye exams for children, yet 66% of caregivers said that none of their children had ever received an eye exam. Participants' major reasons for not bringing their children included the belief that their child had no eye problems along with similar and unique socio-economic barriers. Further information was gained through the use of a five-question test on basic child eye care symptoms, which showed that out of the three country locations, the studied population in India had the least understanding about pediatric eye symptoms. Further analysis revealed significant gaps in understanding of general eye health while detected knowledge barriers provide evidence that fundamental misconceptions appear to be inhibiting caregivers' competence in facilitating their children's eye health.